PENGARUH LOKASI DAN KUALITAS PRODUK DALAM MENENTUKAN MINAT BELI ULANG PADA TOKO INAYAH STORE DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Aisyah, Yunia; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Clothing is the most important element to protect and beautify one's appearance. Along with the development of human life, clothing is usually used as a symbol of status, position, or position of someone who wears it. Therefore, choosing quality clothing products in order to maintain appearance and look elegant in public. The purpose of this study is to analyze and test the Effect of Location and Product Quality on Repurchase Interest at Inayah Stores through Consumer Satisfaction. This research is an explanatory research. The population in this study are consumers of the Inayah Store. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that location has a significant positive effect on consumer satisfaction, product quality has a significant positive effect on consumer satisfaction, location has a significant positive effect on repurchase interest, product quality has no significant positive effect on repurchase interest, Consumer satisfaction has a significant positive effect on repurchase intention. The results of the hypothesis test of location on repurchase intention through consumer satisfaction have a significant positive effect, product quality on repurchase interest through consumer satisfaction has a positive but not significant effect.